Prohibition of Physicians Selling on Social Media: Ethical, Legal, and Professionalism Perspectives - Pamungkas, Luvi Tri; Wening, Nur (Technium Social Sciences Journal, 2025)
The growing practice of physicians selling health products and services through social media has raised serious concerns regarding ethics, law, and professionalism, particularly in maintaining public trust and ensuring patient safety. This study use a Systematic Literature Review (SLR), reviewing 20 Scopus-indexed articles (Q1–Q3) published between 2020 and 2025 that are relevant to the theme of physicians selling on social media. The selection process followed four stages (identification, screening, eligibility, and inclusion) resulting in a final set of articles analyzed qualitatively through narrative synthesis. Bibliometric analysis revealed that dominant issues in the literature include conflicts of interest, insufficient disclosure in sponsored content, blurred boundaries between education and advertising, and the erosion of professionalism leading to diminished public trust. Network and overlay visualizations further indicate a shift in scholarly focus from the benefits of social media toward critiques of commercialization practices, while density visualization highlights that ethical and professionalism issues remain more prominent than legal regulation. These findings affirm that prohibiting physicians from selling products on social media is not merely a normative issue, but a strategic necessity to safeguard clinical objectivity, professional integrity, and consumer protection, while underscoring the urgency of revising medical codes of ethics and strengthening digital health literacy and regulatory frameworks.